2001
DOI: 10.1097/00005392-200106000-00080
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Developmental and Oncogenic Pax2 Gene in Human Prostate Cancer

Abstract: The expression of PAX2 in prostate cancer compared to nonmalignant prostates is statistically significant (Fisher's exact test p = 0.0004). These results suggest a possible role for PAX2 in prostate cancer. Although previous studies have suggested a role for PAX2 for supporting proliferation in undifferentiated cells, no correlation of PAX2 expression with Gleason score was found in prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
3
15
1
Order By: Relevance
“…Indeed, AngII (10 Ϫ9 M) upregulated Pax-2 in MK4 cells ( Figure 1A) but did not induce Pax-2 in MK3 cells ( Figure 1B). Immunostaining seemed intranuclear, consistent with the fact that Pax-2 is a nuclear transcription factor (22,24).…”
Section: Pax-2 Is Visualized In Mk4 But Not Mk3 Cellssupporting
confidence: 68%
See 1 more Smart Citation
“…Indeed, AngII (10 Ϫ9 M) upregulated Pax-2 in MK4 cells ( Figure 1A) but did not induce Pax-2 in MK3 cells ( Figure 1B). Immunostaining seemed intranuclear, consistent with the fact that Pax-2 is a nuclear transcription factor (22,24).…”
Section: Pax-2 Is Visualized In Mk4 But Not Mk3 Cellssupporting
confidence: 68%
“…Aliquots of total RNA (2 g) were used for cDNA synthesis (SuperScript preamplification system; Invitrogen). Subsequently, 2 l of the cDNA reaction mixture was taken to amplify Pax-2 and ␤-actin cDNA fragments using the forward primer 5'-TTTGTGAACGGCCG-GCCCCTA-3' and the reverse primer 5'-CATTGTCACAGATGC-CCTCGG-3', corresponding to the nucleotide sequences n ϩ 622 to n ϩ 642 and n ϩ 902 to n ϩ 922 of Pax-2 cDNA (22). Primers specific for rat ␤-actin (23) (forward and reverse primers 5'-ATGCCATCCT-GCGTCTGGACCTGGC-3' and 5'-AGCATTTGCGGTGCACGAT-GGAGGG-3', corresponding to the nucleotide sequences n ϩ 155 to n ϩ 179 of exon 3 and n ϩ 115 to n ϩ 139 of exon 5 of rat ␤-actin) were used as internal controls.…”
Section: Reverse Transcription-pcr For Pax-2 Mrnamentioning
confidence: 99%
“…24,25 For example, overexpression of HOXC6, PAX2, and BP1 have been described in PCa. [26][27][28] We have previously shown that methylation of homeobox genes is a common event in PCa, 14 whereas others have shown similar results in so-called methylation 'hot spots' within HOX loci. 29,30 In particular, we demonstrated methylation of the HOXD3 region in primary PCa and that this methylation leads to gene silencing in DU-145 cells.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, PAX2 was also detected in these two ER-positive peritoneal mesotheliomas, but not in the PR-positive case in which the patient was a teenage girl. Whether this was due to aberrant expression of PAX2 [40][41][42] in malignant tumors, or Mü llerian metaplastic transformation of malignant mesotheliomas, 43,44 is under further investigation. Nevertheless, PAX2 might be useful as an additional immunohistochemical marker in the differential diagnosis of papillary serous carcinomas of the ovary and female malignant mesotheliomas of the peritoneum, with moderate sensitivity (67%) and specificity (88%).…”
Section: Discussionmentioning
confidence: 99%